Evaluasi Dampak Panjang Program Bantuan Dana Tunai dalam Mengatasi Kemiskinan pada Masyarakat Kota: (Studi pada Warga Pisangan Baru) - Ciek Julyati Hisyam; Lia Karunia Lam Uli Lubis; Agnes Clara Nainggolan; Dela Novi Ardani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to evaluate the long-term impact of the Direct Cash Assistance (BLT) Program on community welfare in Pisangan Baru. BLT is an Indonesian government program that provides direct financial assistance to poor people to reduce poverty. This research uses a qualitative approach with in-depth interviews with four BLT beneficiaries in Pisangan Baru. The research results show that BLT has a significant positive impact on the economic welfare of recipients, being used for basic needs such as food, health and education. However, there are problems in implementation, such as uncertainty about the disbursement schedule and changes in the amount of aid. Even so, the beneficiaries feel helped and hope that this program will continue and be improved. This research concludes that although BLT is effective in reducing the economic burden, improvements are needed in the timeliness of disbursement and transparency of the amount of aid. Recommendations are given to the government to improve the BLT distribution system to make it more effective and efficient, and ensure aid is right on target. It is hoped that these findings will provide input for policy makers in formulating better poverty reduction strategies.